Relationship between serum Chlamydia trachomatis antibody titer and tubal block in infertile Egyptian women - Ahmed Khairy Makled; Osama Saleh Elkady; Khaled Hassan Swedan; Hazem Mohamed Sammour; Elsayed Abdellatif Mohamed (Middle East Fertility Society Journal, 2013)
Objective: This study aimed to investigate the relationship between serum Chlamydia trachomatis antibody titer and tubal block in infertile women. Patients and methods: The study included 80 infertile women scheduled for diagnostic laparoscopy. Using ELISA, the C. trachomatis IgG antibody titer (CAT) was determined in a venous blood sample (5 cc) obtained during laparoscopy. Results: The CAT was positive in 30 patients (23 had tubal block and 7 had patent tubes) and negative in 48 patients (44 had patent tubes and 4 had tubal block). The mean CAT was significantly high (41.7 ± 9.0 U/L) in the infertile patients with tubal block and peritubal adhesion as compared to patients with tubal block only (13.3 ± 3.9 U/L). The latter group had a significantly higher titer than did the women with patent tubes (6.2 ± 3.6 U/L). The CAT values of >8.8 U/L had a sensitivity and specificity of 85.7% and 84.6%, respectively, for tubal occlusion prediction. Conclusion: ELISA can be used as a simple, noninvasive screening test for C. trachomatis IgG antibodies, with a high predictive value for tubal occlusion in infertile Egyptian women, however larger studies are needed to confirm our results.